The Effectiveness of Group Counselling using Cognitive Restructuration Techniques to Improve Students’ Learning Discipline at SMP Muhammadiyah 2 Sawangan - Daffa Rizal Al Ihsan; Aprilia Setyowati (Journal of Education and Counseling (JECO), 2023)
Based on the results of observations, it was found that there were different levels of discipline and there were still students who had a low level of discipline and were less disciplined in obeying school regulations at SMP Muhammadiyah 2 Sawangan and it was found that several students did not take the exams held by the school. There needs to be treatment that can be carried out by counselors to help alleviate problems faced by students, especially regarding learning discipline. This research aims to determine the effectiveness of cognitive restructuring technique group counseling to improve students' learning discipline at SMP Muhammadiyah 2 Sawangan. The type of research used is a pre-experimental quantitative research design with a one-group Pretest-Posttest research design. The sampling technique used in the research was purposive sampling. The research subjects were 6 students from class VIII for the 2022/2023 academic year at SMP Muhammadiyah 2 Sawangan. The validity test uses the product moment formula with the help of the SPSS 25 program. Learning discipline is measured using a learning discipline scale which has been tested for validity and reliability. Of the 34 items tested for validity using the product moment formula, 26 items were valid statements. Meanwhile, the reliability test showed a Chronbach alpha score of 0.624. Based on the research conducted, the results of the Wilcoxon table statistical test hypothesis test were obtained, Asymp. Sig. (2-tailed) of 0.028. Because the value 0.028 < 0.05, Ho is rejected and Ha is accepted. Based on this research, it can be concluded that cognitive restructuring technique group counseling services are effective in improving learning discipline in students.